DESCRIPTIVE ADJECTIVE GROUP (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Descriptive adjective groups consist of adjectives that describe the physical appearance, qualities, or characteristics of nouns. These adjectives provide detailed information to help paint a vivid picture or convey specific attributes of the noun they modify.